Population poverty and policies. - Cp, Timmer (American Economic Review, 1994)
Poverty population and the environment are closely linked with common property resources as the central element explaining externalities within each component. The essential first step in breaking the cycle of poverty is to increase agricultural productivity. Domestic food production must then be raised followed by measures to ensure that these sectoral gains are environmentally and economically sustainable. Appropriate policy would integrate agriculture as an important component of interventions designed to break into the cycle of poverty population and environmental degradation. For agriculture to play such a positive role however governments cannot allow agricultural investments to remain entirely a matter of response to private incentives generated by world markets. These empirical relationships suggest that prices in world markets undervalue the contribution of agriculture to breaking the cycle of poverty as well as its role in sustaining rapid economic growth. Government policies must endeavor to repair these market failures through the nature of their agricultural investments and the design of their policies if the cycle of poverty is to be broken.